2016
DOI: 10.4049/jimmunol.1600822
|View full text |Cite
|
Sign up to set email alerts
|

The Nuclear Receptor AhR Controls Bone Homeostasis by Regulating Osteoclast Differentiation via the RANK/c-Fos Signaling Axis

Abstract: The aryl hydrocarbon receptor (AhR) pathway plays a key role in receptor activator of NF-κB ligand (RANKL)–mediated osteoclastogenesis. However, the mechanism underlying the regulation of AhR expression in osteoclasts and the signaling pathway through which AhR controls osteoclastogenesis remain unclear. We found that the expression of AhR in bone marrow–derived osteoclasts was upregulated by RANKL at an earlier stage than was the expression of signature osteoclast genes such as those encoding cathepsin K and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
48
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 54 publications
(50 citation statements)
references
References 63 publications
2
48
0
Order By: Relevance
“…Recently, we showed that AhR expression was upregulated in bone marrow macrophages (BMMs), similar to c-Fos, 24 h after RANKL treatment. Together with the aforementioned finding that AhR −/− osteoclastic cells have disrupted RANKL-stimulated osteoclastogenic signaling, but normal responsivity to M-CSF [23], these findings suggest that impaired osteoclastogenesis of AhR −/− BMMs may be consequent to RANKL signaling pathway disruption ( Figure 1A). …”
Section: Involvement Of Osteoclast Rankl and Ahr In Immune Regulationsupporting
confidence: 72%
See 4 more Smart Citations
“…Recently, we showed that AhR expression was upregulated in bone marrow macrophages (BMMs), similar to c-Fos, 24 h after RANKL treatment. Together with the aforementioned finding that AhR −/− osteoclastic cells have disrupted RANKL-stimulated osteoclastogenic signaling, but normal responsivity to M-CSF [23], these findings suggest that impaired osteoclastogenesis of AhR −/− BMMs may be consequent to RANKL signaling pathway disruption ( Figure 1A). …”
Section: Involvement Of Osteoclast Rankl and Ahr In Immune Regulationsupporting
confidence: 72%
“…Examining whether AhR plays a role in RANKL/c-Fos/NFATc1 osteoclastogenesis, we found that, compared to control BMMs, BMMs induced to express c-Fos by retroviral gene transfer exhibited a dramatic increase in the number of multinucleated osteoclasts [23]. In the same study, we also showed that RANKL stimulation of BMMs failed to induce osteoclast differentiation in the absence of the AhR-c-Fos complex.…”
Section: Ahr Mediates C-fos Activation In Osteoclastogenesis and Bap-supporting
confidence: 52%
See 3 more Smart Citations